PERAN SANGGAR SENI RWA BHINEDA BAGI PENYANDANG DISABILITAS SENSORIK NETRA DI KOTA DENPASAR - Ni Putu Ratna Dewi Gayatri (Journal Publicuho, 2025)
This paper focuses on the role of the Sanggar Rwa Bhineda art community as a social agent that provides an inclusive and adaptive space for people with visual impairments (Penyandang Disabilitas Sensorik Netra-PDSN).  People with visual impairments are often considered to have limitations that make it difficult for them to carry out their daily activities, including participating in social and cultural spaces. In reality, PDSN who are members of the Rwa Bhineda art community can master traditional Balinese arts and participate in various community activities. Using social capital theory, social inclusion theory, and structural functionalism, this study examines the background of the community's establishment, its role as an inclusive agent, and its impact on PDSN in social and cultural aspects. The analysis was conducted using a qualitative approach focused on understanding and describing in depth the role of the Rwa Bhineda studio as a social agent that provides an inclusive space for PDSN. Data collection was carried out using interviews, observations, and documentation, supported by relevant literature and references. The analysis was conducted qualitatively through interviews, observation, documentation, and literature review. The research findings indicate that PDSN participation is driven by an interest in preserving traditional arts, while the studio not only serves as a platform for artistic expression but also strengthens the social, cultural, and economic roles of people with disabilities in Denpasar City